Integrated farming of stingless bee and pesticide-free chilli fertigation: sharing experience from knowledge transfer project (KTP-RIGS) with Persatuan Anak Kuantan Utara and Organic Farm Venture - Salleh, Mohd Syahmi; Yunus, Muhamad Fahmi; Ahmad, Azmir; Haris @ Harith, Muhammad Salahuddin; Kassim, Salina; Amir, Adibah; Udin, Hashim; Md Yusof, Muhammad Zakiyuddin; Hamid, Muhammad Zulhariz (IIUM Press, 2023)
Persatuan Anak Kuantan Utara (PAKUTA) has been established with the aim of improving the socio-economic well-being of communities especially the B40 families around the Northern Kuantan areas. Through a collaborative effort among PAKUTA, Organic Farm Venture and IIUM, a pilot projecton ‘cili api bara’ fertigation has been conducted under the KTP-RIGS program. This pilot project consists of about 250 polybags of chilli, handled by En Ahmad Bakar who is one of the B40 members of PAKUTA at Kg. Beserah, Kuantan. Several academic staff from IIUM have been invited to be the technical advisors for this project. A colony of stingless bees has also been installed in this pilot project. Apart from the knowledge and skill transfer on Good Agricultural Practices (GAP) of pesticide-free chilli fertigation and stingless bee integrated farming for the B40 members of PAKUTA, additional elements on proper financial record keeping and business documentation along with appropriate post-harvest handling of chilli and stingless bee honey have been also incorporated in this project.